Application of GIS, precision agriculture and unplugging cultivation in plant breeding of Karcag - Czimbalmos, Róbert; Fazekas, Éva Mónika; Murányi, Eszter (Acta Agraria Debreceniensis, 2019)
In the last two decades, the prevailing ecological conditions and climate change have caused negative effects. Therefore, a paradigm shift is needed in the field growing of plants. The latest inventions, digital technologies, precision cultivation are not enough, the mentality of the farmers is more important. For this reason, not only big financial sacrifices, but adequate receptivity are needed on behalf of farmers. Adequate skills and continuous self-education are necessary. The yield of plant growing farms is determined by ecological conditions to a 40% extent, genetic background of the seed has a 30% share and the applied agricultural technology has a proportion of 30%. In different agroecological conditions, bred varieties of plants have bigger tolerance to unfavorable factors of the regions and significant yield stability. Farmers, who buy and sow seeds, can only contribute to the genetic potential of the seeds with cultivation technology. Plant breeding provides stable genetic background and good quality seeds. Breeding activity – choosing variety proposants, breeding them, selection work, classical breeding process for 8-10 years – must create new landraces, which can produce balance, high yield and have good quality parameters in extreme ecological conditions, yearly excursion and have higher tolerance to unfavorable factors of the region giving significant production stability for farmers. In Karcag GIS technology, precision cultivation elements and soil-friendly agrotechnical methods have been introduced which largely support the aims of breeding and can also provide optimal cultivation conditions in extreme years. Because of the specificity of breeding the main aim is not only to increase yield but to provide harmonic growing for bred materials, to decrease the number and the cost of cultivation and to be punctual. In this study, applied new methods and technologies are introduced.